METHADONE VERSUS BUPRENORPHINE: TO STUDY THE EPIDEMIOLOGY AND COMPARE THE TREATMENT OUTCOME AS IN RETENTION RATE BETWEEN METHADONE AND BUPRENORPHINE TAKING OPIOID DEPENDENT PATIENTS FROM OST CENTER - RAJIV ARORA; SHINY DEHAL; NEERU BALA; KHUSHBINDER SINGH; HARSHPREET SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective is to study sociodemographic profile and compare retention rate between methadone and buprenorphine (BPN) taking opioid-dependent patients from opioid substitution therapy (OST) centers. Methods: Two hundred patients, 100 each on methadone and BPN already taking treatment from OST center under the Department of Psychiatry, GMC Amritsar and Civil Hospital, Kapurthala, were studied. The precise aim of the interview and the nature of the study were explained to the enrolled patients and patients were reassured about the confidentiality of the information given. In this 1-year study, patients were followed up at 3, 6 and 9 months and compared to find the drug associated with higher patient retention on treatment. Hence, establishing which drug is more effective in treatment adherence. Results: The majority of patients, that is, about 80% in the BPN group and 93% in the methadone group were below 40 years of age. In the BPN group, 70% of subjects were married persons (70%) compared to 74% in the methadone group. Most patients in both groups were educated up to 10th and 12th standards. Most of the patients in both groups had duration of substance dependence between 5 and 10 years. In the BPN group, 51% of participants had previously attempted some treatment for drug abuse while in the methadone group, 57% had attempted the same. Conclusion: After comparing the retention between the two drug groups, no statistically significant difference was found.